POLITIK HUKUM PIDANA PERSETUBUHAN ANAK DI BAWAH UMUR MENGGUNAKAN RESTORATIVE JUSTICE YANG DI LAKUKAN OLEH HAKIM SEBAGAI PEMBAHARUAN HUKUM PIDANA DALAM RANGKA MEWUJUDKAN TUJUAN HUKUM - Hasaki, Nero Mika; Sudjiarto, Tatok; Pandiangan, Hendri Jayadi (Collegium Studiosum Journal, 2024)
Criminal Law Policy can also be called a Criminal Law policy or can also be called Penal Policy or Criminal Law reform. In implementing a Criminal Law Policy, it means an effort to realize criminal legislation that is in accordance with the circumstances and situations at a certain time and for the future. One of the implementations of a legal policy, especially what the author wants to discuss, namely Criminal Law Policy in the implementation of laws and regulations, is in the context of Restorative Justice arrangements, which is a settlement of cases or Criminal Law problems outside the Criminal Justice System. Settlement of Criminal cases outside the court using modern dispute resolution or problem resolution methods greatly changes criminal law reform, but a settlement of cases or Criminal Law problems involving Legal Subjects in the form of victims, perpetrators, families of victims and perpetrators, as well as the community and parties interested in a Criminal act or problem that occurs to reach an agreement and settlement between each party who has a problem or case. With the settlement of criminal cases using out-of-court dispute resolution using Restorative Justice, it is a new model of dispute resolution that has an impact on criminal law renewal and realizes the objectives of the law itself. The research method used by the author in writing this thesis is the normative legal research method, namely legal research carried out by examining library materials or secondary data only. This research is also called library material research. The concept of Restorative Justice has been applied in Decision No. 27 / Pid.Sus / 2022 / PN. Jkt.Pst,. and has fulfilled the sense of justice for the Defendant and for the victim, because the Defendant is ready to marry witness Thalia Bunga Chalista when he finishes college and until now between the Defendant and witness Thalia Bunga Chalista in this case have not been harmed even until now the Defendant and Witness Thalia Bunga Chalista still have good communication.